Measuring intention to use IP-Belt among pregnant mothers using TAM Model: technology-based innovation in road safety / Wan Mohd Farid Wan Zakaria... [et al.] - Wan Zakaria, Wan Mohd Farid; Musa, Mohd Hafizan; Azman Ong, Mohd Hanafi; Burhanuddin, Muhammad Addin; Haris, Sharazad (UiTM Cawangan Johor, 2019)
This study presents the behavioural intention to use an innovation of a safety belt specially developed for pregnant mothers, named IP-Belt. This newly developed innovation aims to enhance the safety of these pregnant mothers when they are behind the wheel, or as passengers; and this research is done as an extension to the development of this innovation. Technology Acceptance Model (i.e. TAM) was adopted in predicting the behavioural intention to use the IP-Belt. A survey was conducted among pregnant mothers to see their intention to use the said innovation. The data was analysed using the Structural Equation Modelling technique with Partial Least Square estimation theory. The analysis indicated that Perceived Ease of Use and Perceived Usefulness had a positive significant influence towards Attitude and Trust, whereas all other variables (i.e. Perceived Ease of Use, Perceived Usefulness, Attitude, and Trust) also significantly influenced behavioural intention to use the IP-Belt. In addition, the study indicated that Attitude and Trust had a partial mediating effect towards the relation of Perceived Ease of Use and Perceived Usefulness towards behavioural intention to use the IP-Belt.